Juego dramático, una experiencia creativa (2014)
This text brings together the journey undertaken in the construction and staging of a idea, of a work that took shape over time, through images and children's bodies; is a witness to the culmination of a dream, adventure companion of Bottom and his friends is a journey through the universe of theater. It is a journey that hopes to go beyond this experience, which hopes to have left a mark, a good memory, a countless number of sensations, hopes, and a possible future in art, in love and in coexistence.